The Price of Surviving on Adrenaline: Developmental Programming Responses to Chronic Fetal Hypercatecholaminemia Contribute to Poor Muscle Growth Capacity and Metabolic Dysfunction in IUGR-Born Offspring - Gibbs, Rachel L.; Yates, Dustin T. (Frontiers in Animal Science, 2021)
Maternofetal stress induces fetal programming that restricts skeletal muscle growth capacity and metabolic function, resulting in intrauterine growth restriction (IUGR) of the fetus. This thrifty phenotype aids fetal survival but also yields reduced muscle mass and metabolic dysfunction after birth. Consequently, IUGR-born individuals are at greater lifelong risk for metabolic disorders that reduce quality of life. In livestock, IUGR-born animals exhibit poor growth efficiency and body composition, making these animals more costly and less valuable. Specifically, IUGR-associated programming causes a greater propensity for fat deposition and a reduced capacity for muscle accretion. This, combined with metabolic inefficiency, means that these animals produce less lean meat from greater feed input, require more time on feed to reach market weight, and produce carcasses that are of less quality. Despite the health and economic implications of IUGR pathologies in humans and food animals, knowledge regarding their specific underlying mechanisms is lacking. However, recent data indicate that adaptive programing of adrenergic sensitivity in multiple tissues is a contributing factor in a number of IUGR pathologies including reduced muscle mass, peripheral insulin resistance, and impaired glucose metabolism. This review highlights the findings that support the role for adrenergic programming and how it relates to the lifelong consequences of IUGR, as well as how dysfunctional adrenergic signaling pathways might be effective targets for improving outcomes in IUGR-born offspring.